أساليب تعليم مهارة الكلام عبر الإنترنت و وسائله التكنولوجية و المعلومات - Nikmatus Sakdiah; Khoirul Jamil (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In the era of information technology, the approach of teaching Arabic language teachers in developing speaking skills must change. Currently, the traditional methods used in teaching speaking skills in Arabic are considered outdated and less developed compared to modern techniques used in teaching other languages. Arabic language teachers should take advantage of available technology, such as the internet, to make the process of learning speaking skills more engaging, creative, and motivating. The use of the internet in teaching speaking skills is considered an important step in developing the learning process. Teachers can utilize various internet resources to present interactive and engaging lessons that stimulate student participation and enhance their understanding of the topics discussed. Multimedia resources such as instructional videos and interactive resources on the internet can be used to expand students' understanding and stimulate them to learn more effectively. Study results indicate that speaking skill learning methods and internet-based media have a significant impact on improving students' speaking skills. These modern methods can make the learning process more effective and suitable for students' needs in the era of information technology.